Does irrigation have an impact on food security and poverty: Evidence from Bwanje Valley Irrigation Scheme in Malawi - Nkhata, Rudolf (International Food Policy Research Institute, 2014)
The purpose of this study was to assess the impact of irrigation on household food security and poverty using a case study of Bwanje Valley Irrigation Scheme in Malawi. The results also showed a positive impact of irrigation on daily per capita caloric intake, with both groups of irrigating farmers realizing similar improved levels of caloric intake over farmers that did not participate in the irrigation scheme. In addition, traditionally marginalized groups - households headed by youth, female-headed households, and low-income households - earned more agricultural income than what they would have earned if they did not participate in the irrigation scheme.